Market power and the role of banks as liquidity providers in GCC markets - Ritab Al-Khouri; Houda Arouri (Cogent Economics & Finance, 2019)
Purpose: The study aims to discuss the role of market power and the banks as a liquidity provider, specifically in the twenty-first century. Design: The empirical investigation has evaluated the effects of market power on the ability of GCC banks to provide and transform liquidity. Findings: The banks conveniently perform two significant functions as the financial institution; therefore, they are known to play the role of risk transformers. They have been recognized as the important entities of liquidity creators and providers. The increase in market power increases the ability of GCC banks to create liquidity. There is a negative association between Inflation, growth in GDP, and ability of bank to produce liquidity. Conclusion: The financing impediments are reinforced due to increased competition among different banks. The demand of loans is likely to increase, when the investors possess valuable investment projects during expansion. The study recommends that the future research must involve off-balance-sheet items in the investigation for further clarification.
Keywords: 330; Bank; liquidity; Gulf Cooperation Council (GCC); loans; market power